Análise integrada do nexo água-energia-emissões e mitigação das externalidades para o estado de Minas Gerais - Leonardo Barrouin Melo (2020)
The energy supply of a state or country is a permanent concern, since it requires well-structured planning and operation. Population growth, territorial expansion for housing, competition for water use, the finitude of fossil energy reserves and the lack of consistent and continuous energy planning are some of the existing problems. In addition, research points climate change as one of the greatest challenges that humanity will face next decades in this century, and that will also affect energy production. Historically, energy matrix of Minas Gerais state has the peculiarity of being predominantly renewable; 53.7% of total demand was met by renewable sources in 2017. This percentage is highly sensitive to extreme weather events, which may result in changes in state energy matrix. The associated externalities are related to the greater exposure to toxic gases emitted, due to the increased share of more polluting energy sources. In this work, an integrated analysis of the water-energy-emissions nexus for Minas Gerais state was carried out, as well as the mitigation of the present externalities. To achieve the objectives of the study, two computational models combined in an integrated approach were used: WEAP - Water Evaluation and Planning and the LEAP - Low Emissions Analysis Platform. The focus of the analysis was concentrated on the electric matrix of Minas Gerais state, through the modeling of hydropower plants. The main results include the reduction in hydropower generation to the end of the study, 2019 to 2049, between -16.8% and -7.8% in water restriction scenarios. Final electricity demand, in reference scenario, increased 40.8% in this period and, in energy scenarios, there was increase between 63.6% and 89.5%. There were significant electricity generation increases by fossil fuel thermoelectric plants and, in all scenarios studied, there was also a significant increase in CO2eq emissions. Electrical system expansion planning must involve non-hydraulic plants capacity increasing as way of ensuring the state's energy security.